STEM-10. UPSTREAM REGULATORS OF THE GLIOMA STEM CELL PHENOTYPE. (12th November 2021) - Calinescu, Alexandra; Sultan, Zain; Kauss, McKenzie; Al-Holou, Wajd; Heth, Jason
Abstract: Glioblastoma (GBM) is the most common and deadly primary brain tumor in adults. Recurrence of the disease is attributed in part to the presence of Glioma Stem Cells (GSC), which are resistant to chemo- and radiotherapy and can initiate tumor formation. Molecularly, GSCs resemble the mesenchymal subtype that is associated with worse prognosis. GSCs share many characteristics with Neural Stem Cells (NSCs) including proliferative potential, migratory capacity, telomerase activity, diverse progeny and similar gene signature, however differ fundamentally from NSCs in their tumor forming ability. RNA-Seq analysis of GSCs and NSCs illustrates significant enrichment in GSCs of transcription factors (TFs) known to be dysregulated in cancer, chief among them being SIX1, a developmental TF with documented roles in progression of multiple cancers. Overexpression of SIX1 in A172 GBM cells enhances proliferation, promotes resistance to radiotherapy and alters expression of a core set of 4 developmental TFs (POU3F2, SALL2, OLIG2 and SOX2) capable to reprogram differentiated GBM cells into GSCs (Suva et al., 2014). Analysis of SIX1 in surgical samples from glioma patients illustrates that high expression of SIX1 correlates with tumor grade, finding corroborated in the TCGA and CGGA data sets. Surprisingly, primary NSCs, after extended time in culture, increase their proliferation rate, acquire a mesenchymal transcriptional signature akin to GSCs, including high expression of SIX1, and form deadly tumors when implanted into the brains of mice. Comparing the epigenetic landscape of transformed and normal NSCs we identify a significant enrichment of accessible chromatin at promoter and enhancer loci in transformed NSCs, including at regulatory regions of SIX1 and of genes that define mesenchymal GBM. These data suggest that SIX1 may represent an upstream regulator of the GSC phenotype and may drive malignant transformation of NSCs. Genetic and epigenetic loss of function analyses are ongoing to test this hypothesis.